Diseño organizacional y la gestión del talento humano en la agencia de productos médicos Apromed de la ciudad de Loja. - Gálvez Espinosa., Santiago Israel (2012)
The organizational designs and the appropriate use of the human talent cooperate to achieve an administrative and operative systematizing since they transform into instruments for a modern efficient communication and of rational administration. The present investigation work is guided to elaborate an instrument that allows to give a contribution regarding the administration of the management from the human talent to the agency of medical products APROMED, of the City of Loja, in the same one that is evidenced that the lack of an Organizational Structure and an inadequate system of the management of the Human Talent. To give solution to this problem they thought about the following objectives: To carry out a diagnosis for the agency of medical products APROMED of the City of Loja; To design the flowcharts and administrative manuals for the agency in study; To execute a rating of having put by points for the agency study object; To elaborate the evaluation of the personnel's acting that he/she works in APROMED of the city of Loja. To give execution to the objectives outlined in the project you uses the methods and technical following: Scientific Method: for the elaboration of the theoretical mark; Deductive Method: to obtain general concepts on the study topic and at the same time to go elaborating favorable new concepts to the acting of the Agency; Inductive Method: to determine conclusions, and recommendations Analytic Method: for the identification and study of each one of the functions that characterize the newspaper to live off the Agency.; Historical Method: to know the history of the company, and like he/she has come evolving with spending of the years until the present time; Mathematical Method: it served in the rating method as having put by points, through the application of the mathematical formulas; the direct Observation: to establish the current situation of the institution, and to determine this way the sectors where they concentrate the problems; He/she interviews: to know the manager's opinions; It interviews: to apply the personnel of the Agency of medical products APROMED of the city of Loja. The results obtained jurisdiction the following ones: The agency doesn't have administrative tools as: flowcharts, administrative manuals and personnel specialized in the handling of the human talent, it doesn't possess Manual of Welcome; in what refers to the admission stages of personal it is not applied, as for recruitment he/she carries out it through friend's recommendations or family, in what refers to personnel's recruiting it should be adjusted to the law with the purpose of not having in the later thing any problem of labor type with the personnel that works in the agency, in the induction phase a welcome manual he/she settles down whose purpose is the one of making them know people that newly enter to work to the agency, outstanding information of the organization. They think about the conclusions and following recommendations: The agency of medical products doesn't possess any type of flowcharts; it lacks Manuals of Functions and manual of Welcome, they lack an admission process, the qualification doesn't exist, the personnel is motivated, because they offer them incentives inside the Company, the salary or wage is in function to personal approaches, and not to what corresponds to the work, experience, abilities, knowledge, responsibilities and risks that he/she has each employee. After having concluded the investigation work I present the following recommendations: The Agency of medical products should carry out planning to get advance and development and this way to take the planned works ahead; it should have a structural, functional flowchart, and posicional with the purpose of establishing each one of the departments, this way to define the positions that possess according to its abilities and dexterity, the employees' experience; it should increase and it should welcome the proposal of the manual of functions and to apply, with the objective that the personnel that works knows what function it should complete; they should execute the admission (recruitment, selection, recruiting, induction and qualification) process that I am proposing for this way to obtain the personnel's equal distribution, in each position to act.